2013
DOI: 10.1016/j.topol.2012.10.015
|View full text |Cite
|
Sign up to set email alerts
|

The fundamental group as a topological group

Abstract: This paper is devoted to the study of a natural group topology on the fundamental group which remembers local properties of spaces forgotten by covering space theory and weak homotopy type. It is known that viewing the fundamental group as the quotient of the loop space often fails to result in a topological group; we use free topological groups to construct a topology which promotes the fundamental group of any space to topological group structure. The resulting invariant, denoted π τ 1 , takes values in the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
64
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 23 publications
0
64
0
Order By: Relevance
“…Endowed with the quotient topology induced by the natural surjective map q : Ω k (X, x) → π k (X, x), where Ω k (X, x) is the kth loop space of (X, x) with the compact-open topology, the familiar homotopy group π k (X, x) becomes a quasitopological group which is called the quasitopological kth homotopy group of the pointed space (X, x), denoted by π qtop k (X, x) (see [2,3,4,13]). Biss [2] proved that π qtop 1 (X, x) is a topological group.…”
Section: Introductionmentioning
confidence: 99%
“…Endowed with the quotient topology induced by the natural surjective map q : Ω k (X, x) → π k (X, x), where Ω k (X, x) is the kth loop space of (X, x) with the compact-open topology, the familiar homotopy group π k (X, x) becomes a quasitopological group which is called the quasitopological kth homotopy group of the pointed space (X, x), denoted by π qtop k (X, x) (see [2,3,4,13]). Biss [2] proved that π qtop 1 (X, x) is a topological group.…”
Section: Introductionmentioning
confidence: 99%
“…Calcut and McCarthy [7] proved that the quotient topology induced by the compact-open topology of the fundamental group of a locally path connected and semilocally simply connected space is discrete which implies that π qtop 1 (X, x 0 ) is a topological group. Brazas [4] introduced a new topology on fundamental groups made them topological groups. Torabi et al [15] showed that π qtop 1 (X, x 0 ) is a topological group when X is a locally path connected, semilocally small generated space.…”
Section: On the Whisker Topology And Sltl Spacesmentioning
confidence: 99%
“…For more details, see [1,2,4]. Also, π τ 1 (X, x) is the fundamental group endowed with another topology introduced by Brazas [3]. In fact, the functor π τ 1 removes the smallest number of open sets from the topology of π qtop 1 (X, x) so that make it a topological group.…”
Section: The Topology Of Spanier Subgroupsmentioning
confidence: 99%
“…In [3], it is proved that topological fundamental groups of shape injective spaces are Hausdorff. Since the spaces with trivial Spanier group are not necessarily shape injective (see [6, Step 18, Section 6]), triviality of Spanier groups can not certify the Hausdorffness of topological fundamental groups in general.…”
Section: The Topology Of Spanier Subgroupsmentioning
confidence: 99%